(untitled) (Scientific journal of the Fergana State University, 2025)
The article is devoted to the problems of creating terminological apparatus and metalanguage for studying proverbs and sayings as universal language units characteristic of any language system, in which there has been made an attempt by the authors to generalize and unify the existing terms related to proverbs and sayings and to work out terminological apparatus and metalanguage for their research.